Immigration worldwide policies, practices, and trends - Segal, Uma Anand; Elliott, Doreen; Mayadas, Nazneen S. (Nazneen Sada) (New York ; Oxford : Oxford University Press, 2010)
This volume explores current patterns and policies of immigration in key countries and regions across the globe and analyzes the implications for these countries and their immigrant populations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Emigration and immigration -- Government policy -- Case studies; Human beings -- Migrations -- Case studies; Migrations of nations -- Case studies; Human capital -- Case studies